Electronic Structure of the Rare-Earth Dihydride GdH₂ - Ayat, Z.; Daoudi, B.; Ouahab, A.; Boukraa, A. (Металлофизика и новейшие технологии, 2015)
With the WIEN2k simulation code, the ab initio calculations of electronic properties for the cubic stoichiometric rare-earth dihydride GdH₂ (in the cubic fluorite structure) are performed using the full-potential linearized augmented plane wave (FP-LAPW) method approach within the density functional theory (DFT) in the generalized gradient approximation (GGA) (used for the exchange—correlation potential). The lattice parameter, the bulk modulus, its pressure derivative, the density of states, and the energy band structures are determined. Two low-lying hydrogen—metal bands of GdH2 are observed. The Fermi energy EF falls at a level where most of the states are rare-earth 5d conduction states. Information on the negligible role of the H1s state contribution near EF is obtained.